1993
DOI: 10.1136/emj.10.3.220
|View full text |Cite
|
Sign up to set email alerts
|

Nurse triage in theory and in practice.

Abstract: 'Nurse Triage' refers to the formal process of early assessment of patients attending an accident and emergency (A&E) department by a trained nurse, to ensure that they receive appropriate attention, in a suitable location, with the requisite degree of urgency. The benefits claimed for nurse triage include better patient outcomes, through clinical management reaching those in greatest need of it first. A recent study of nurse triage in a British A&E department failed to demonstrate the benefits claimed: patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…It is also recommended that physiotherapy can be offered as a primary management option [6]. Similarly, improving the clinical skills of general practitioners in managing specific musculoskeletal problems is also advisable [7].…”
Section: Discussionmentioning
confidence: 99%
“…It is also recommended that physiotherapy can be offered as a primary management option [6]. Similarly, improving the clinical skills of general practitioners in managing specific musculoskeletal problems is also advisable [7].…”
Section: Discussionmentioning
confidence: 99%
“…35 This work produced a series of provocative letters and papers and raised questions about decisions made using triage data, including the national performance tables. 8,[36][37][38][39] In 1997 the Manchester Triage Group published its book Emergency Triage to establish a national triage scale for the UK. 15 The NHS soon thereafter adopted the MTS as developed by the Manchester Triage Group to be used by all NHS A & Es.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Five-level triage scales have been developed in recent years, including the Australasian Triage Scale (ATS, Australia and New Zealand), the Canadian Triage and Acuity Scale (CTAS, Canada), the Manchester Triage System (MTS, United Kingdom [UK]), and the Emergency Severity Index (ESI, United States). [6][7][8] Like the three-level triage models, the ATS, CTAS, and MTS are based on the urgency of patients' conditions and seek to answer the question, ''How long can patients wait?'' Research has shown the ATS and the CTAS to be reliable, and the ATS has also been validated with clinical outcomes.…”
mentioning
confidence: 99%
“…The CECSS was classified into five-point Likert-type rating scale demonstrating the degree of satisfaction with each statement. Possible responses ranged from strongly disagree (1) to strongly agree (5). A higher score represents a higher degree of satisfaction with emergency nursing.…”
Section: A-subjects Designmentioning
confidence: 99%
“…Triage refers to sorting or sifting. (4,5) Triage is the process of determining the priority of emergency patients treatments based on the severity of their condition and priority of emergency Sahar Mahmoud El-Khedr Abd El-Gawad: Improving Children Emergency Care Satisfaction through Standardized Approach of Pediatric Triage transport. Triage aims to promote the safety of patients by ensuring that timing of care and resource allocation is requisite to the degree of illness or injury.…”
Section: Introductionmentioning
confidence: 99%